ANALISIS PELAYANAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN (PBB ) PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN SIGI - Ponulele, Akhirfan S. (Katalogis, 2016)
The purpose of this research are: (1) Determining and describing the Property Tax Collection Services at Office for Management of Regional Revenue, Finance and Assets of Sigi regency; and (2) Indetifying and describing the obstacle factors in the implementation of property tax collection services at Office for Management of Regional Revenue, Finance and Assets of Sigi regency. This is a descriptive research with qualitative approach gained from in-depth interviews. Location of research is at the Office for Management of Regional Revenue, Finance and Assets of Sigi regency. Informants consist of employees in BPHTB and PBB-P2 of Office for Management of Regional Revenue, Finance and Assets of Sigi regency as the service providers and community as the service recipients of Property Tax Collection. Data sources include primary data and secondary data with data collection implemented through observation, interviews, and documentation. Data analysis is conducted using descriptive analysis techniques with qualitative approach illustrating that the Property Tax Collection Services at Office for Management of Regional Revenue, Finance and Assets of Sigi regency has accomplished in accordance with the expectations of society as a taxpayer, and the existence of barriers in Property Tax Collection Services at Office for Management of Regional Revenue, Finance and Assets of Sigi regency are still found.